Preparation method of glass fiber reinforced flame-retardant PBT (polybutylene terephthalate) engineering plastic with high heat resistance and low warpage
By adding a low -warning PBT mother -granules and other auxiliary agents to the PBT resin, combined with the special processing method of the dual screw extruder, the problem of warming the warranty PBT material of the glass fiber and the low thermal deformation temperature , Achieve the effect of high heat resistance and low warp.
Patent Information
- Application Number
- CN202411457096.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
AI Technical Summary
Existing glass fiber reinforced flame retardant PBT materials are prone to warping problems during injection molding, and the thermal deformation temperature is low in high temperature environments, which limits its application range.
By adding low -warp PBT mother grains, ester exchange inhibitors, ester switching inhibitors and organic/inorganic composite nuclei to the PBT resin, control the ester exchange reaction, increase the thermal deformation temperature of the material, and squeeze it through double screws. The special processing method of the aircraft will reduce the phenomenon of warmers.
It significantly improves the thermal deformation temperature of the material, reaching 170 to 200 ° C. At the same time, it maintains the low -warming characteristics, and meets the high temperature heat resistance requirements in the field of automotive and electronic appliances.
Smart Images

Figure CN119371784A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified engineering plastics and relates to a method for preparing high-heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastics. Background Art
[0002] The performance of PBT resin that has not been modified is average, and its mechanical strength and heat deformation temperature are low. In order to improve the mechanical strength and heat deformation temperature of PBT resin, the most effective method used is to use glass fiber (glass fiber) reinforcement. Although glass fiber reinforcement can greatly improve the mechanical strength and heat deformation temperature of PBT resin, it will bring about warping problems. This is because the special needle-like structure of glass fiber is mostly arranged parallel to the flow direction during the injection molding process, resulting in inconsistent longitudinal and lateral shrinkage rates of the product after cooling and shaping, resulting in warping, especially when injecting large products and thin-walled products. It is more prone to warping and deformation, affecting the use and appearance of the product. On this basis, some studies have obtained PBT engineering plastics with excellent flame retardant properties by adding flame retardants, broadening the application of modified PBT engineering plastics.
[0003] In order to solve the warping problem of glass fiber reinforced flame retardant PBT materials, Patent 201711126363.X discloses a low-warping flame retardant material and its preparation method, which achieves a balance between rigidity and toughness, improves the anisotropy of the material, and controls the warping of the material through different combinations of inorganic fillers and glass fibers. However, the main strength of the material is provided by glass fiber. If a large amount of inorganic fillers is used to replace glass fiber, although good low-warping characteristics can be achieved, a large amount of replacement of glass fiber will lead to a significant reduction in material strength, limiting the application range of the material.
[0004] In order to solve the above problems, some studies have added a certain proportion of crystallization-inhibiting polymers, such as PET, PC, ASA and other polymers, to glass fiber reinforced flame-retardant PBT engineering plastics. These polymers can change the orderly arrangement of glass fibers in the material and reduce the warping characteristics; but due to the presence of these crystallization-inhibiting polymers, they will undergo ester exchange reactions with PBT resin, thereby reducing the thermal deformation temperature of the material and limiting the application of the material in high temperature environments.
[0005] To this end, Patent 202011340933.7 discloses a glass fiber reinforced PBT / PC alloy with high strength, low warpage and heat deformation temperature, and its preparation method and application. The ester exchange inhibitor polycarbodiimide is added during the extrusion process to inhibit the ester exchange reaction and increase the heat deformation temperature of the material. However, the maximum heat deformation temperature in this patent is only 150°C, which limits the application of the material in environments with temperature resistance requirements and still needs to be further improved.
[0006] Therefore, it is of great significance to study a preparation method of high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics to solve the problems existing in the prior art. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing high-heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastics.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a high-heat-resistant, low-warpage glass fiber reinforced flame-retardant PBT engineering plastic, comprising the steps of firstly adding a premix to a twin-screw extruder for melting, then feeding a flame retardant and glass fiber into the twin-screw extruder from a side feed port, respectively, and mixing with the molten premix, and then extruding a strip from a die of the twin-screw extruder after mixing, and finally cooling the strip in a cooling water tank, and then pelletizing the strip in a pelletizer to obtain a high-heat-resistant, low-warpage glass fiber reinforced flame-retardant PBT engineering plastic;
[0010] The premix is obtained by uniformly mixing PBT resin II, low warpage PBT masterbatch, compatibilizer, crystallization inhibiting polymer, flame retardant synergist, inorganic filler, nucleating agent and other additives in a high-speed mixer;
[0011] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0012]
[0013] The crystallization inhibiting polymer is one or more of PC resin, PET resin, AS resin and ASA resin;
[0014] Low warpage PBT masterbatch is obtained by mixing PBT resin I, ester exchange inhibitor, ester exchange inhibitor synergist and other additives in a high-speed mixer, and then melt-extruding and granulating through a twin-screw extruder.
[0015] The transesterification inhibitor is anhydrous sodium dihydrogen phosphate or alkyl phosphate, and the transesterification inhibition synergist is epoxy resin;
[0016] In the low warpage PBT masterbatch, the mass percentages of PBT resin I, ester exchange inhibitor, ester exchange inhibitor synergist and other additives are 82-96%, 2-8%, 1-5% and 1-5%, respectively;
[0017] The nucleating agent is an organic / inorganic composite nucleating agent, which is composed of an organic nucleating agent and an inorganic mineral nucleating agent in a mass ratio of 0.2 to 2:1; the inorganic mineral nucleating agent is ultrafine talcum powder, and the organic nucleating agent is sodium benzoate, sodium montanate or vinyl ion copolymer.
[0018] The present invention first prepares a low-warpage PBT masterbatch, during the preparation of the masterbatch, the ester exchange inhibitor has consumed the catalyst remaining in the PBT resin (a certain catalyst needs to be added to the polyester material during the polymerization reaction so that the reaction proceeds smoothly, but these catalysts generally remain in the resin, and the residual catalyst will catalyze the ester exchange reaction between PBT and other materials such as PET and PC, so the ester exchange inhibitor is needed to complex the catalyst in the polyester to make it lose its catalytic effect), and the epoxy resin as an ester exchange inhibition synergist reacts with the terminal hydroxyl group and the terminal carboxyl group in the PBT resin during the preparation of the masterbatch, thereby reducing the end group concentration in the masterbatch, and the low-warpage PBT masterbatch is used as a raw material for preparing PBT engineering plastics. Since the PBT resin and the low-warpage PBT masterbatch are the same substance, the fusion effect between them is good. Therefore, in this processing process, on the one hand, the low-warpage masterbatch preferentially consumes the catalyst remaining in the PBT resin, and on the other hand, referring to the similar compatibility theory, the epoxy resin will react better with the end group in the enhanced flame-retardant PBT engineering plastic in the masterbatch than when added alone, thereby improving the ester exchange inhibition reaction. In addition, the present invention also adds an organic / inorganic composite nucleating agent to act on the crystal region where the crystallization performance of PBT is reduced due to the ester exchange reaction, thereby compensating for the reduction in thermal deformation temperature caused by the ester exchange reaction and further enhancing the thermal stability of the glass fiber reinforced flame retardant PBT engineering plastics.
[0019] As the preferred technical solution:
[0020] A method for preparing a high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastic as described above, wherein the heat deformation temperature of the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastic is 170-200°C;
[0021] The high heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastic was injection molded into a rectangular sheet with a length of 100mm, a width of 100mm, and a thickness of 0.8mm. The maximum warping height tested did not exceed 0.7mm.
[0022] In the method for preparing the high heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastics as described above, the intrinsic viscosity of PBT resin I is 0.7-0.85 dL / g, and the intrinsic viscosity of PBT resin II is 0.7-1.0 dL / g.
[0023] In the method for preparing the high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics as described above, the flame retardant is one or more of brominated triazine, brominated polystyrene, brominated polycarbonate, brominated epoxy resin and decabromodiphenylethane.
[0024] In the method for preparing the high heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastics as described above, the glass fiber is one or more of a circular cross-section glass fiber and a flat cross-section glass fiber.
[0025] The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic as described above, wherein the diameter of the circular cross-section glass fiber is 10 to 15 μm and the length is 2 to 6 mm;
[0026] The flat cross-section glass fiber has a cross-section flatness ratio of 2 to 6 and a length of 3 to 6 mm.
[0027] A method for preparing a high-heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic as described above, wherein the compatibilizer is a graft copolymer of glycidyl methacrylate (GMA) and an elastomer, and the elastomer is a polyolefin elastomer (POE), ethylene-methyl acrylate or ethylene-butyl acrylate;
[0028] The flame retardant synergist is one or more of sodium antimonate, antimony trioxide and antimony pentoxide;
[0029] The inorganic fillers are three or more of mica powder, talc powder, barium sulfate, silicon dioxide, calcium carbonate and inorganic salt whiskers; different types of fillers have different appearances and morphologies, mica powder has a distinct lamellar structure, talc powder has a lamellar structure, barium sulfate and calcium carbonate are fine particles, silicon dioxide has a spherical structure, and inorganic salt whiskers have a needle-like structure. Fillers with different appearances and morphologies are interlaced with each other in the system, similar to the random distribution of special-shaped steel bars at the pouring position before pouring concrete. In high-heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic products, inorganic fillers with different structures can be randomly distributed and interlaced with each other, disrupting the directional distribution of glass fibers to cause the material to crystallize and orient, thereby inhibiting warping;
[0030] Other additives are antioxidants and lubricants. The antioxidant is one or more of antioxidant 1010, antioxidant 168 and antioxidant 412S. The lubricant is PETS (pentaerythritol stearate).
[0031] In the method for preparing the high heat-resistant, low warpage glass fiber reinforced flame-retardant PBT engineering plastic as described above, when the high heat-resistant, low warpage glass fiber reinforced flame-retardant PBT engineering plastic is prepared from the premix, flame retardant and glass fiber, the processing temperature of the twin-screw extruder is 220-260°C.
[0032] In the method for preparing the high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics as described above, when preparing the low-warpage PBT masterbatch, the processing temperature of the twin-screw extruder is 220-245°C.
[0033] Principle of the invention:
[0034] Warping is a common phenomenon in glass fiber reinforced composites, which is mainly caused by the uneven shrinkage of different components in the material during the curing or cooling process. The orientation of glass fiber in the flow direction limits the shrinkage of resin, and the induced crystallization of resin around glass fiber strengthens this effect. This uneven shrinkage leads to the warping of glass fiber reinforced composites. The purpose of adding crystallization inhibiting polymer is to evenly weaken the induced crystallization effect of glass fiber on the surrounding PBT resin to achieve low warpage characteristics, but the addition of crystallization inhibiting polymer also weakens the crystallization of PBT resin (PBT resin and PET resin and PC resin as crystallization inhibiting polymers all contain ester groups, terminal hydroxyl groups and terminal carboxyl groups, which makes them very easy to trigger ester exchange reactions in the blending system, first generating block copolymers and finally forming random copolymers, destroying the regularity of the chain segments and making the crystallization performance worse; in addition, the addition of ASA and AS block copolymers will also reduce the system crystallization performance), resulting in a lower heat deformation temperature of low warpage PBT composite materials.
[0035] In order to deal with the above problems, the present invention has carefully designed the formula of the ester exchange inhibitor and the ester exchange synergist, which effectively curbs the ester exchange reaction between PBT and the crystallization inhibiting polymer in the form of low warpage masterbatch, reduces the formation of random copolymers, and coordinates through the composite nucleating agent to improve the overall crystallization performance of the system, unlike glass fiber, which only induces crystallization of the surrounding PBT resin. Specifically, firstly, the catalyst remaining in the PBT resin is consumed by the ester exchange inhibitor, effectively reducing the ester exchange reaction between ester groups; secondly, the epoxy resin used as the ester exchange inhibitor synergist in the present invention is easy to react with the terminal hydroxyl group and the terminal carboxyl group due to the high activity of the epoxy group, reducing the concentration of the terminal group participating in the ester exchange reaction, thereby inhibiting the ester exchange reaction. However, the combination of the ester exchange inhibitor and the ester exchange synergist will inevitably cause a certain degree of ester exchange reaction and affect the thermal deformation temperature of the material, limiting the application of the material in an environment with temperature resistance requirements. Therefore, the present invention adds an organic / inorganic composite nucleating agent to act on the crystal region where the crystallization performance of PBT is reduced due to the ester exchange reaction, thereby compensating for the reduction of the heat deformation temperature caused by the ester exchange reaction and effectively enhancing the thermal stability of the material.
[0036] According to the "nucleation-growth" theory, the crystallization process of polymers is divided into two stages: nucleation and growth. The present invention uses ultrafine talcum powder as an inorganic mineral nucleating agent, which can induce the orderly arrangement of molecular chains and thus efficiently form crystal nuclei; at the same time, the compatibility between organic nucleating agents and polymers is higher than that of inorganic mineral nucleating agents, which is more conducive to the growth of crystal nuclei. Therefore, by compounding organic and inorganic nucleating agents and synergizing with ester exchange inhibitors and their synergists, the present invention successfully constructs an efficient system and effectively improves the thermal deformation temperature of the material.
[0037] Beneficial effects:
[0038] (1) The preparation method of the high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic of the present invention significantly improves the thermal deformation temperature of the material under the combined action of an ester exchange inhibitor, an ester exchange inhibition synergist and an organic / inorganic composite nucleating agent, thereby expanding the high-temperature and heat-resistant use requirements of the low-warpage modified PBT engineering plastic.
[0039] (2) The present invention provides a method for preparing a highly heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastic. The material has good low-warping properties and a high heat deformation temperature, meeting the market application requirements of the automotive and electronic and electrical appliance fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The present invention is a flow chart of a preparation method of a highly heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastic. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] The raw material information used in the embodiments and comparative examples of the present invention is as follows:
[0043] PBT resin I: KH2075 with a viscosity of 0.75dL / g and KH2080 with a viscosity of 0.8dL / g produced by Kanghui New Material Technology Co., Ltd. are selected.
[0044] PBT resin II: KH2083 produced by Kanghui New Material Technology Co., Ltd. is selected.
[0045] Compatibilizer I: Glycidyl methacrylate grafted ethylene-methyl acrylate copolymer, AX8900 produced by SK Chemicals was selected.
[0046] Compatibilizer II: Glycidyl methacrylate grafted polyolefin elastomer, KT3505 produced by Ketong Plastics is selected.
[0047] PC resin 1300-10NP produced by LG Chemical was selected.
[0048] PET resin, KH2678C produced by Kanghui New Material Technology Co., Ltd.
[0049] AS resin, NF2200 produced by Formosa Plastics Co., Ltd.
[0050] The ASA resin used was PW957 produced by Chi Mei Chemical.
[0051] Ester exchange inhibitor I: alkyl phosphate, WSFR-PX220 produced by Zhejiang Wansheng was selected;
[0052] Ester exchange inhibitor II: anhydrous sodium dihydrogen phosphate, produced by Shifang Zhixin Technology.
[0053] Ester exchange inhibitor synergist: epoxy resin, CYD-011 produced by Baling Petrochemical.
[0054] Flame retardant synergist I: Antimony trioxide produced by Shanxing Antimony Industry, with a purity of 99.8%.
[0055] Flame retardant synergist II: Sodium antimonate produced by Zhuzhou Ante.
[0056] Mica powder: CJ-H4 produced by Wanqiao.
[0057] Calcium carbonate: CC1250 produced by Haicheng Guangyuan.
[0058] Barium sulfate: B2800 produced by Youkuang Plastic New Materials.
[0059] Talc: SK7800 produced by Haicheng Jinghua.
[0060] Inorganic salt whiskers: NP-S12 produced by Fengzhu New Materials.
[0061] Silica: Commercially available hydrophobic silica.
[0062] Antioxidant 1010 and Antioxidant 168: Both are produced by BASF.
[0063] Antioxidant 412S: Produced by Tianjin Lianlong.
[0064] Lubricant: PETS, PETS-AP produced by Italy Faji.
[0065] Organic nucleating agent I: sodium benzoate.
[0066] Organic nucleating agent II: vinyl ion copolymer, Surlyn 8920 produced by Dow Chemical.
[0067] Organic nucleating agent II I: sodium montanate, P252 produced by Clariant.
[0068] Inorganic mineral nucleating agent: ultrafine talc, HTP ultra5L produced by IMIFABI.
[0069] Flame retardant I: brominated epoxy resin, CXB-2000H produced by Yujin, South Korea;
[0070] Flame retardant II: brominated polystyrene, 7010 produced by Shandong Xurui;
[0071] Flame retardant IIⅠ: brominated polycarbonate, BC-58 produced by LANXESS Chemicals is selected.
[0072] Circular cross-section glass fiber Ⅰ: The glass fiber ECS10-4.5-534A produced by Jushi is selected, with a diameter of 10μm and a length of 4.5mm;
[0073] Circular cross-section glass fiber II: The glass fiber ECS13-03-534A produced by Jushi is selected, with a diameter of 13μm and a length of 3mm.
[0074] Flat cross-section glass fiber: The flat glass fiber ECS4F-03-534A produced by Jushi is selected, with a cross-section flatness ratio of 4 and a length of 3mm.
[0075] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0076] (1) Warpage characteristics: A rectangular thin sheet sample of 100 mm × 100 mm × 0.8 mm was prepared by a plastic injection molding machine at an injection temperature of 240-275°C. The maximum warpage height was tested. The smaller the warpage height, the better the low warpage of the material surface.
[0077] (2) Heat resistance: According to ISO 75-1-2013 standard, the heat deformation temperature of the material under a weight of 1.8 MPa is tested. The higher the heat deformation temperature, the higher the ambient temperature that the material can withstand.
[0078] (3) Tensile strength and elongation at break: tested in accordance with ISO 527-1-2012.
[0079] (4) Vertical burning grade: tested in accordance with UL94 standard.
[0080] Example 1
[0081] A method for preparing high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics, such as Figure 1 As shown, the specific steps are as follows:
[0082] (1) Preparation of raw materials:
[0083] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0084]
[0085] PBT resin I, ester exchange inhibitor I, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0086] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0087]
[0088] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer I, crystallization inhibitor polymer, flame retardant synergist I, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0089] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant I and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0090] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0091] Example 2
[0092] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0093] (1) Preparation of raw materials:
[0094] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0095]
[0096] PBT resin I, ester exchange inhibitor I, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0097] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0098]
[0099] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer I, crystallization inhibitor polymer, flame retardant synergist I, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0100] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant I and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0101] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0102] Example 3
[0103] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0104] (1) Preparation of raw materials:
[0105]
[0106] PBT resin I, ester exchange inhibitor I, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0107] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0108]
[0109] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer I, crystallization inhibitor polymer, flame retardant synergist I, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0110] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant I and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0111] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0112] Example 4
[0113] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0114] (1) Preparation of raw materials:
[0115] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0116]
[0117] PBT resin I, ester exchange inhibitor I, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0118] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0119]
[0120] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer I, crystallization inhibiting polymer, flame retardant synergist, inorganic filler, nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0121] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant I and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0122] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0123] Example 5
[0124] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0125] (1) Preparation of raw materials:
[0126] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0127]
[0128] PBT resin I, ester exchange inhibitor I, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0129] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0130]
[0131] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer I, crystallization inhibiting polymer, flame retardant synergist, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0132] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant I and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0133] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0134] Example 6
[0135] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0136] (1) Preparation of raw materials:
[0137] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0138]
[0139] PBT resin I, ester exchange inhibitor, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0140] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0141]
[0142] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer II, crystallization inhibitor polymer, flame retardant synergist, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0143] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant ⅡⅠ and the glass fiber are fed into the twin-screw extruder from the side feeding port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0144] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0145] Example 7
[0146] A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, the specific steps are as follows:
[0147] (1) Preparation of raw materials:
[0148] The amount of each raw material component in the low warpage PBT masterbatch is as follows:
[0149]
[0150] PBT resin I, ester exchange inhibitor II, ester exchange inhibitor synergist, antioxidant I and lubricant I are uniformly mixed in a high-speed mixer, and then melt-extruded and granulated by a twin-screw extruder with a processing temperature in each zone ranging from 220 to 245°C to obtain a low-warpage PBT masterbatch.
[0151] The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows:
[0152]
[0153] (2) PBT resin II, low warpage PBT masterbatch, compatibilizer II, crystallization inhibitor polymer, flame retardant synergist I, inorganic filler, organic / inorganic composite nucleating agent, antioxidant II and lubricant II are uniformly mixed in a high-speed mixer to obtain a premix.
[0154] (3) First, the premix is added to a twin-screw extruder with a processing temperature in each zone ranging from 220 to 260°C for melting, and then the flame retardant II and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic.
[0155] The performance indicators of the finally obtained high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are shown in Table 1.
[0156] Table 1
[0157]
[0158] Comparative Example 1
[0159] A method for preparing glass fiber reinforced flame retardant PBT engineering plastics is basically the same as that in Example 1, except that no ester exchange inhibitor synergist is added to the low warpage PBT masterbatch.
[0160] The heat deformation temperature of the glass fiber reinforced flame retardant PBT engineering plastic finally obtained is 160.8℃.
[0161] By comparing Comparative Example 1 with Example 1, it can be found that the heat deformation temperature of Comparative Example 1 is significantly reduced. This is because the epoxy resin, which serves as an ester exchange inhibition synergist, reacts with the terminal carboxyl and terminal hydroxyl groups of the PBT resin to reduce the terminal group concentration, reduce the reaction sources for ester exchange, and better inhibit the ester exchange reaction. Therefore, the heat deformation temperature of Comparative Example 1 without adding an ester exchange inhibition synergist is low.
[0162] Comparative Example 2
[0163] A method for preparing glass fiber reinforced flame retardant PBT engineering plastics is basically the same as that of Example 1, except that no organic / inorganic composite nucleating agent is added to the raw materials.
[0164] The heat deformation temperature of the glass fiber reinforced flame retardant PBT engineering plastic finally obtained is 165.7℃.
[0165] By comparing Comparative Example 2 with Example 1, it can be found that the heat deformation temperature of Comparative Example 2 is reduced. This is because the random copolymer generated by the ester exchange reaction reduces the overall molecular weight of the blending system, and the random copolymer generated in the system reduces the crystallization performance of the resin. The addition of an organic / inorganic composite nucleating agent in Example 1 and the dispersion of ultrafine talcum powder in the system are more conducive to the formation of crystal nuclei. The organic nucleating agent has better compatibility with the resin than the inorganic mineral nucleating agent, and is more conducive to the growth of crystal nuclei. The combined effect improves the crystallinity of the material and the heat deformation temperature.
[0166] Comparative Example 3
[0167] A method for preparing glass fiber reinforced flame retardant PBT engineering plastics is basically the same as that of Example 1, except that no ester exchange inhibitor synergist and organic / inorganic composite nucleating agent are added to the raw materials.
[0168] The heat deformation temperature of the glass fiber reinforced flame retardant PBT engineering plastic finally obtained is 151.3℃.
[0169] By comparing Comparative Example 3 with Example 1, it can be found that the heat deformation temperature of Comparative Example 3 is significantly reduced. This is because the use of the ester exchange inhibitor alone can only consume the residual catalyst in the masterbatch to a certain extent, and cannot reduce the terminal carboxyl and terminal hydroxyl groups that can participate in the ester exchange reaction like the addition of the ester exchange inhibitor synergist, so the effect of inhibiting the ester exchange reaction is not obvious enough; in addition, when the organic / inorganic composite nucleating agent is not added, the decrease in heat deformation temperature caused by the ester exchange reaction cannot be compensated, so the heat deformation temperature of Comparative Example 3 is significantly reduced.
Claims
1. A method for preparing high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics, characterized in that: First, the premix is added to a twin-screw extruder for melting, and then the flame retardant and the glass fiber are fed into the twin-screw extruder from the side feed port, respectively, and mixed with the molten premix. After mixing, a strip is extruded from the die of the twin-screw extruder, and finally the strip enters a cooling water tank for cooling, and then is pelletized by a pelletizer to obtain a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic; The premix is obtained by uniformly mixing PBT resin II, low warpage PBT masterbatch, compatibilizer, crystallization inhibiting polymer, flame retardant synergist, inorganic filler, nucleating agent and other additives in a high-speed mixer; The amounts of the raw material components in the high heat-resistant and low warpage glass fiber reinforced flame-retardant PBT engineering plastics are as follows: The crystallization inhibiting polymer is one or more of PC resin, PET resin, AS resin and ASA resin; Low warpage PBT masterbatch is obtained by mixing PBT resin I, ester exchange inhibitor, ester exchange inhibitor synergist and other additives in a high-speed mixer, and then melt-extruding and granulating through a twin-screw extruder. The transesterification inhibitor is anhydrous sodium dihydrogen phosphate or alkyl phosphate, and the transesterification inhibition synergist is epoxy resin; In the low warpage PBT masterbatch, the mass percentages of PBT resin I, ester exchange inhibitor, ester exchange inhibitor synergist and other additives are 82-96%, 2-8%, 1-5% and 1-5%, respectively; The nucleating agent is an organic / inorganic composite nucleating agent, which is composed of an organic nucleating agent and an inorganic mineral nucleating agent in a mass ratio of 0.2 to 2:1; the inorganic mineral nucleating agent is ultrafine talcum powder, and the organic nucleating agent is sodium benzoate, sodium montanate or vinyl ion copolymer.
2. The method for preparing a high heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: The heat deformation temperature of high heat resistance and low warpage glass fiber reinforced flame retardant PBT engineering plastics is 170-200℃; The high heat-resistant and low-warping glass fiber reinforced flame-retardant PBT engineering plastic was injection molded into a rectangular sheet with a length of 100mm, a width of 100mm, and a thickness of 0.8mm. The maximum warping height tested did not exceed 0.7mm.
3. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: The intrinsic viscosity of PBT resin I is 0.7 to 0.85 dL / g, and the intrinsic viscosity of PBT resin II is 0.7 to 1.0 dL / g.
4. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: The flame retardant is one or more of brominated triazine, brominated polystyrene, brominated polycarbonate, brominated epoxy resin and decabromodiphenylethane.
5. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: The glass fiber is one or more of a circular cross-section glass fiber and a flat cross-section glass fiber.
6. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 5, characterized in that: The diameter of circular cross-section glass fiber is 10-15 μm and the length is 2-6 mm; The flat cross-section glass fiber has a cross-section flatness ratio of 2 to 6 and a length of 3 to 6 mm.
7. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: The compatibilizer is a graft copolymer of glycidyl methacrylate and an elastomer, and the elastomer is a polyolefin elastomer, ethylene-methyl acrylate or ethylene-butyl acrylate; The flame retardant synergist is one or more of sodium antimonate, antimony trioxide and antimony pentoxide; The inorganic filler is three or more of mica powder, talc, barium sulfate, silicon dioxide, calcium carbonate and inorganic salt whiskers; Other additives are antioxidants and lubricants. The antioxidant is one or more of antioxidant 1010, antioxidant 168 and antioxidant 412S, and the lubricant is PETS.
8. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: When high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastics are prepared from premix, flame retardant and glass fiber, the processing temperature of the twin-screw extruder is 220-260°C.
9. The method for preparing a high heat-resistant and low-warpage glass fiber reinforced flame-retardant PBT engineering plastic according to claim 1, characterized in that: When preparing low warpage PBT masterbatch, the processing temperature of the twin-screw extruder is 220-245°C.
Citation Information
Patent Citations
Low warpage flame retardant material and preparation method thereof
CN107759985A
A glass fiber reinforced PBT / PC alloy with high strength, low warpage and high heat distortion temperature, its preparation method and application
CN112625404B
High toughness, low warpage and high fluidity glass fiber reinforced PET / PBT / PC alloy and preparation method thereof
CN102952376A
Special low-warpage flame-retardant reinforced PBT (polybutylene terephthalate) material for relay and application of material
CN103724953A
Reinforced flame-retardant PBT / PET alloy and preparation method thereof
CN111534060A
Cited By
Double-drawing PBT release film and preparation method thereof
CN120248397A
A double-stretch PBT release film and its preparation method
CN120248397B
Low-warpage composite PC reinforced material and preparation method thereof
CN121045792A
Hydrolysis-resistant PBT (polybutylene terephthalate) reinforced material capable of being subjected to laser welding and preparation method of hydrolysis-resistant PBT reinforced material
CN121471673A